The nearby astrometric-spectroscopic binary star Hip 68682 - Xia, Fang; Wang, Xiaoli; Fu, Yanning; Chen, Yue (Frontiers in Astronomy and Space Sciences, 2023)
The nearby Astrometric-Spectroscopic Binary star Hip 68682 has an orbital period of ~9.88 yr. The dynamical state (component masses and kinematic parameters) of this system is redetermined by fitting all the observational data available to us, including the radial velocity data (RVD), the relative position data (RPD), and the Hipparcos Intermediate Astrometric Data (HIAD). The precision-weighted sum of squared residuals calculated from our results is significantly smaller than the previous ones. With the simulated data based on CSST (Chinese Space Station Telescope), the relative orbit could be improved further. Based on the known apparent magnitude information and the fitted parallax parameter 60.59 +/- 0.36 mas, we derive the absolute V magnitudes of the two components as 5.21 mag and 8.91 mag, respectively. The component masses are determined as 0.98 +/- 0.06 M_sun and 0.49 +/- 0.06 M_sun. These improved dynamical masses are helpful to constrain the lower end of the stellar empirical mass–luminosity relation (MLR). However, significant improvement of MLR for this mass region still needs more data with accuracy better than ~3%.